Association of Age and Gender with the BMI of Obese Individuals in Lahore, Pakistan - Mustafa, Faheem; Munir, Farwa; Munir, Mubbasher; Riaz, Saba; Bacha, Umar; Tahir, Hafsa; Baig, Atif Amin (BioScientific Review, 2022)
Obesity is a serious public health concern. It is expanding exponentially across the globe and is associated with chronic diseases, such as Type II diabetes and cardiovascular diseases. The aim of the current study was to find the association among age, gender, and Body Mass Index (BMI) of obese individuals residing in Lahore, Pakistan. This cross-sectional study was carried out in January 2021. Data was collected through an electronic questionnaire. A total of 868 individuals (84.3% female and 15.7% male) of ages between 18 to 60 years participated in the current study. Convenient sampling method was used. Anthropometrics including weight, height, and age were taken in kilograms (kg), centimeters (cm) and years, respectively. The standard equation to calculate BMI was used (weight in kg/height in m²). WHO BMI cut-points for Asians were used to assess the BMI status of the selected individuals. Statistical analysis was carried out through Microsoft Excel and SPSS. It was found that the prevalence of obesity was 17.2% (12% Type I obesity, while 2.6% Type II and Type III obesity), while 15.1% participants were found to be overweight, 22.7% were underweight, and 44.9% were determined to be normal. It was also determined that the prevalence of underweight, overweight, Type I, Type II, and Type III obesity is more common among women (20.6%, 12.3%, 9.2%, 2.3%, and 2%, respectively) than men (2.1%, 2.8%, 2.8%, 0.3%, and 0.7%, respectively) (p-value <0.05), indicating a positive association. The highest prevalence of underweight, overweight, Type I, Type II, and Type III obesity was observed in age group 19-21 years (11.1%, 7.3%, 7.4%, 1.5%, and 2.1%, respectively) (p-value <0.05). These results would help to develop public health programs and preventive measures to reduce the prevalence of the above risk factors for obesity and other non-communicable diseases.